Early sodium bicarbonate infusion was associated with improved outcome in critically ill patients with acute moderate metabolic acidosis: a retrospective observational study - Sai Huang; Bo Yang; Yaojun Peng; Libo Wang; Lili Wang; Jing Wang; Xuan Zhou; Hanyu Zhu; Li Chen; Cong Feng (Emergency and Critical Care Medicine)
Abstract. Background. Sodium bicarbonate (SB) infusion is widely administered for severe metabolic acidosis (MA). However, evidence supporting its effect on mortality in patients with acute moderate MA (MMA) has not yet been established. This study investigated the effect of early SB administration on mortality in critically ill patients with acute MMA and in other subgroups. Methods. We retrospectively analyzed a large intensive care unit (ICU) database, Medical Information Mart for Intensive Care (MIMIC)-IV. Patients with acute MMA were identified using MIMIC-IV. Propensity score analysis (PSA) was performed to explain baseline differences in the probability of receiving SB. The marginal structural Cox model (MSCM) was developed to adjust for both baseline and time-varying confounding variables. The primary outcome was ICU mortality, and the secondary outcome was hospital mortality. Results. In total, 1738 patients with acute MMA were identified; 484 were enrolled in the SB group and 1254 in the non-SB group. In the PSA, early SB infusion was not associated with reduced ICU mortality (hazard ratio [HR]: 0.88; 95% confidence interval [CI]: 0.67–1.14; P = 0.33) in the overall cohort. However, it was associated with improved ICU survival in patients with sepsis (HR: 0.69; 95% CI: 0.48–0.99; P < 0.05), sepsis shock (HR: 0.61; 95% CI: 0.40–0.93; P < 0.05), and sepsis and lactic acidosis (lactate >2.2 mmol/L; HR: 0.69; 95% CI: 0.48–0.99; P < 0.05). The results from MSCM were similar to those obtained for PSA. Conclusion. Early SB infusion was associated with improved ICU survival outcomes in critically ill adult patients with sepsis, septic shock, and sepsis and lactic acidosis and acute MMA. Further large randomized controlled trials are required to confirm these results.